2018
DOI: 10.1007/s10546-018-0415-x
|View full text |Cite
|
Sign up to set email alerts
|

Consistent Boundary-Condition Treatment for Computation of the Atmospheric Boundary Layer Using the Explicit Algebraic Reynolds-Stress Model

Abstract: Standard turbulence models for the atmospheric boundary layer (ABL) typically use boundary conditions based on the Monin-Obukhov similarity theory (MOST). This can lead to inconsistency between the boundary condition and the closure model. Here, we propose a new boundary-condition treatment of the stratified ABL, derived for the so-called explicit algebraic Reynolds-stress model. The boundary conditions correspond to the relations for vanishing buoyancy effects that are valid close to the ground. The solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…This will have a fundamental influence on the wake development and the performance of wind parks. The extension of the EARSM to non-neutral conditions has over recent years been developed by Lazeroms et al (2013), andŽeli et al (2019) have subsequently demonstrated the model's capability of capturing these effects. This will be of interest for future wind turbine wake studies.…”
Section: Discussionmentioning
confidence: 99%
“…This will have a fundamental influence on the wake development and the performance of wind parks. The extension of the EARSM to non-neutral conditions has over recent years been developed by Lazeroms et al (2013), andŽeli et al (2019) have subsequently demonstrated the model's capability of capturing these effects. This will be of interest for future wind turbine wake studies.…”
Section: Discussionmentioning
confidence: 99%
“…A rough wall model relates the surface flux to the aerodynamic roughness length, giving the well-known logarithmic law of the wall that is strictly valid only for the neutrally stratified atmospheric boundary layer and vanishing pressure gradient [16]. However, close to the surface, buoyancy effects are usually negligible, and turbulence is predominately produced by shear effects [16]. Thus, the rough wall function for a neutrally stratified environment was also applied to the SBL case.…”
Section: Cfd Equations and Numerical Methodsmentioning
confidence: 99%
“…Thus, the rough wall function for a neutrally stratified environment was also applied to the SBL case. Above this lower part of the logarithmic layer, turbulence can be strongly affected by buoyancy forces, and, in this case, corrections to the logarithmic law are introduced through MOST [16], as described below.…”
Section: Cfd Equations and Numerical Methodsmentioning
confidence: 99%
“…RANS turbulence for both CBL and SBL is on the other hand completely isotropic in the freestream, which as earlier discussed is expected from Boussinesqtype RANS turbulence models. More sophisticated RANS turbulence models such as explicit algebraic Reynolds stress models [22,23] and uncertainty-quantification models [24][25][26] can predict anisotropic freestream turbulence, but are also more complex to implement compared to standard two-equation models.…”
Section: Reynolds Stresses and Anisotropymentioning
confidence: 99%